Electroreduction of Chlorine Gas at Platinum Electrodes in Several Room Temperature Ionic Liquids: Evidence of Strong Adsorption on the Electrode Surface Revealed by Unusual Voltammetry in Which Currents Decrease with Increasing Voltage Scan Rates - Huang, X; Silvester, D; Streeter, I; Aldous, L; Hardacre, C; Compton, R (2008)
Voltammetry is reported for chlorine, Cl2, dissolved in various room temperature ionic liquids using platinum microdisk electrodes. A single reductive voltammetric wave is seen and attributed to the two-electron reduction of chlorine to chloride. Studies of the effect of voltage scan rate reveal uniquely unusual behavior in which the magnitude of the currents decrease with increasing scan rates. A model for this is proposed and shown to indicate the presence of strongly adsorbed species in the electrode reaction mechanism, most likely chlorine atoms, Cl·(ads). © 2008 American Chemical Society.